2020
DOI: 10.3390/nu12061629
|View full text |Cite
|
Sign up to set email alerts
|

Association between Low Protein Intake and Mortality in Patients with Type 2 Diabetes

Abstract: The aim of this study was to investigate the association between protein intake and mortality risk in patients with type 2 diabetes. We analyzed a pooled data of 2494 diabetic patients from two prospective longitudinal studies. Nutritional intake was assessed using a Food Frequency Questionnaire at baseline. Protein intake per body weight (kg) per day was categorized into quartile groups. Adjusted hazard ratios (HRs) and 95% confidence interval (CI) were calculated using Cox regression analysis. During the six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…We slightly modified the previous variables 20 in accordance with the previous study. 28 Analyses were carried out using the two models (crude model, not adjusted; adjusted model, adjusted for age, sex, body mass index, HbA1c level, systolic blood pressure, total cholesterol level, estimated glomerular filtration rate and frequency of hypoglycemic event). Patients with missing data in the analyses were excluded (complete case analysis).…”
Section: Discussionmentioning
confidence: 99%
“…We slightly modified the previous variables 20 in accordance with the previous study. 28 Analyses were carried out using the two models (crude model, not adjusted; adjusted model, adjusted for age, sex, body mass index, HbA1c level, systolic blood pressure, total cholesterol level, estimated glomerular filtration rate and frequency of hypoglycemic event). Patients with missing data in the analyses were excluded (complete case analysis).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in very old mice, high protein diet reduced mortality whereas low protein diet remarkably reduced body weight and increased mortality [179]. The pooled analysis of the J-EDIT and the JDCS also demonstrated that the lowest quartile of protein intake was associated with highest mortality after adjustment for covariates in patients with diabetes aged 75 years or older but not in those aged younger than 65 years [131].…”
Section: Age-related Differences In Nutritional Intake On Health Outcmentioning
confidence: 92%
“…We analyzed the data pooled from the J-EDIT and the Japan Diabetes Complications Study (JDCS), which originally intended to validate the effect of lifestyle intervention on prevention of diabetic complications [130]. We found that those with low protein intake (<0.92 g/kg/body weight) showed significantly higher mortality, especially in those aged 75 years or older [131]. Since diabetes is a well-known risk factor for sarcopenia, sufficient protein intake should be recommended in older patients with diabetes except for those with end-stage renal failure.…”
Section: Proteinsmentioning
confidence: 99%
“…Therefore, the impact of nutrients on health outcomes may vary with age [ 31 ]. It has been reported that the risk of death is increased in those with type 2 diabetes older than 75 years who have low protein, vegetable, and fish intakes [ 32 , 33 ]. Elderly patients with type 2 diabetes should have their dietary intake monitored not only for excessive sodium intake, but also for intakes other food groups and nutrition intakes that occur with low sodium intake to avoid dietary habits that would lead to malnutrition, sarcopenia, frailty development of diabetic complications and death.…”
Section: Discussionmentioning
confidence: 99%